PANDANGAN ETIKA KRISTEN TERHADAP IDENTITAS HOMOSEKSUAL - Christopher Alexander; Ferry Simanjuntak (Diegesis : Jurnal Teologi, 2021)
The issue of homosexuality continues to be debated everywhere, both in psychology, biology and in theology. Arguments are exchanged to maintain the gay and opposing views of each other. The issue of homosexual identity is even more. The gay gene is the ultimate weapon launched by pro homosexuals to provide a protective wall for homosexuals. The self-justification of homosexuality also helps to be supported by using the bible as its proponency. On this occasion, the writer raised the topic "A Christian Ethic View Of Homosexual Identity" to try to help each homosexual to realize that they had never been created in such a state. And the bible clearly says that being a homosexual is a sin (Romans 1:24-27). God has never created a person with homosexual sexual orientation, it is evident with God creating Adam and Eve from the beginning, which means that the sexual orientation God desires is heterosexual. Homosexuals then have to confess their sins before God, repent, and ask God's grace to enable them to escape the sin of homosexuality. Because God's forgiveness and grace are always available to those who will humble them to come to Him. Keywords: Christian Ethic; Homosexuality; Homosexual Identity; Gay Gene; Genetic.